The Rhetorical Moves in Indonesian EFL Graduate Students’ Thesis Abstracts - Erma Sujiyani (General English Education, 2022)
Rhetoric in an abstract writing literally means the techniques a writer might use to deliver complicated information in a limited amount of space effectively and intentionally. However, as being non-native speaking (NNS) writers, Indonesian EFL Graduate students often have difficulties in producing, organizing, and delivering ideas of an abstract into widely accepted international standard of English academic writing conventions. This study describes the nature and characteristics of the rhetoric of thesis abstract focusing on the moves-step(s) written by Indonesian EFL Graduate Students of Palangka Raya University. The model proposed by Samraj (2002) consisting of five moves: Move 1– Situating the Research, Move 2–Purpose, Move 3–Methods, Move 4–Results, and Move 5–Conclusion was used as a general guideline to analyze the moves-step(s) of the abstracts. The findings of the study show that three textual spaces: M2-Purpose, M3-Methods, and M4-Results are compulsory while the other two (M1-Situating the Research and M5-Conclusion) are optional; and the rhetorical pattern mostly employed in the abstracts is PMRC or M2-M3-M4-M5. However, in realizing the rhetorical strategies of the abstracts, a great deal of first language rhetorical interference (such as redundancy use of steps particularly in M2, reordering or non-linear patterns of steps mostly the steps in M3, the overlap function between moves especially between M4 and M5, the low occurrence of M1, and the repeated use of embedding moves particularly the embedment of M2 and M3) is discovered among the moves or the steps forming each move.